Chemical composition of the essential oil of Calocedrus macrolepis Kurz from Ha Giang province - Hung, Nguyen Quang; Thai, Tran Huy; Dai, Do Ngoc; Laffont-Schwob, Isabelle (Academia Journal of Biology, 2012)
The stem oil of Calocedrus macrolepis Kurz collected from Ha Giang province, Vietnam, in May 2008 was isolated by steam distillation to give oil yield 0.15% and analyzed by Capillary GC and GC/MS. Thirty eight components have been identified accounting more than 78.7% of the oil respectively. The major constituents of this oil appeared to be benzoic acid (23.3%) and dodecan-7 ol (14.6%). Less predominant constituents included trimethylenehexane (7.3%), α-terpineol (6.6%), 1,3-cyclooctadiene (5.8%), 4-nitrostyrene (2.8%), undecane (2.7%), methyllenebornane (2.3%), tricyclene (2.3%), tricyclo (2.0%) and cavacrol methyl ther (1.1%). All the other components were in concentration of less than 0.1-0.9%.